Antiphospholipid antibodies increase the levels of mitochondrial DNA in placental extracellular vesicles: Alarmin-g for preeclampsia. Issue 1 (December 2017) - Tong, Mancy; Johansson, Caroline; Xiao, Fengyi; Stone, Peter; James, Joanna; Chen, Qi; Cree, Lynsey; Chamley, Lawrence
Abstract The pathogenesis of preeclampsia remains unclear but placental factors are known to play a crucial role causing maternal endothelial cell dysfunction. One potential factor is placental micro- and nano- vesicles. Antiphospholipid antibodies (aPL) increase the risk of preeclampsia ten-fold, in part by damaging the mitochondria in the syncytiotrophoblast. Since mitochondrial DNA (mtDNA) is a danger- associated molecular pattern (DAMP/alarmin) that may activate endothelial cells, the aims of the current study were to investigate whether aPL affect the number of placental vesicles extruded, their mtDNA content and their ability to activate endothelial cells. Exposure of first trimester human placental explants to aPL affected neither the number nor size of extruded micro- and nano- vesicles (n = 5), however their levels of mtDNA were increased (n = 6). These vesicles significantly activated endothelial cells (n = 5), which was prevented by blocking toll-like receptor 9 (TLR-9), a receptor for extracellular DNA. Thus, aPL may increase the risk of preeclampsia in part by increasing the amount of mtDNA associated with placental vesicles. That mitochondrial DNA is recognised as a DAMP by TLR-9 to cause endothelial cell activation, raises the possibility that placental vesicles or TLR-9 might be a target for pharmaceutical intervention to reduce the consequences of aPL in pregnancy.